Detection of NO in a spark-ignition research engine using degenerate four-wave mixing - Grant, A; Ewart, P; Stone, C (2002)
We report the first application of degenerate four-wave mixing (DFWM) to combustion diagnostics in a methane-fuelled internal combustion research engine. Combustion-generated NO in the spark-ignited engine was detected using scanning narrowband DFWM in a modified forward folded BOXCARS geometry. The resulting spectra of the X2∏-A2 ∑+ (0, 0) band at 226 nm display an excellent signal-to-noise ratio. Extension of the technique to different engine operating conditions and to time-resolved multiplex DFWM is discussed. © Springer-Verlag 2001.